Cryopreservation of Indonesian native chicken semen by using dimethyl sulfoxide and various level of ethylene glycol as cryoprotectants - KHAERUDDIN KHAERUDDIN; JUNAEDI JUNAEDI; HASTUTI HASTUTI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Khaeruddin, Junaedi, Hastuti. 2020. Cryopreservation of Indonesian native chicken semen by using dimethyl sulfoxide and various level of ethylene glycol as cryoprotectants. Biodiversitas 21: 5718-5722. Imported purebred chickens are becoming more popular and a regular staple in Indonesia. Therefore, it is necessary to strengthen conservation efforts to preserve Indonesian chickens, one of which is by means of sperm cryopreservation. This study aimed to determine the effects of the addition of DMSO and different concentrations of ethylene glycol to a Ringer’s lactate egg yolk (RLY)-or coconut water egg yolk (CWY)-based extender on the quality of frozen-thawed Indonesian chicken sperm. This study was used nine Indonesian native roosters about 20 months of age. The semen extenders used in this study were RLY + DMSO 7%, RLY + ethylene glycol 3%, RLY + ethylene glycol 5%, RLY + ethylene glycol 7%, CWY + DMSO 7%, CWY + ethylene glycol 3%, CWY + ethylene glycol 5% and CWY + ethylene glycol 7%. Liquid semen was packaged in 0.25 mL straw, then cooled at 5oC for 2 hours, frozen at 5 cm above liquid nitrogen for 10 minutes, following stored in a liquid nitrogen container for 24 hours. The semen straws were thawed at 37oC for 30 seconds. Statistical analysis for multiple comparisons was performed as a completely randomized design with eight treatment levels and seven replications. The results showed that there were no differences in sperm motility, recovery rate, and abnormality between extenders after the freeze-thaw process. Whereas, RLY + DMSO 7% was the highest sperm viability.